Agrotechnical Requirements of Preparation of Field Row for Repeated Crop Planting (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Effective and high-quality harvest from the vine plant is important in many aspects of row-to-row cultivation. In this case, the vine plant is not only effective in absorbing nutrients from the soil, but also effective from the cultivated area its use was considered an effective method in the fight against diseases and pests.